"Let's Hook Up When the Pandemic is Over:" Latinx Sexual Minority Men's Sexual Behavior During COVID-19. Issue 8 (13th October 2021) - Harkness, Audrey; Weinstein, Elliott R.; Atuluru, Pranusha; Vidal, Ronald; Rodriguez-Diaz, Carlos E.; Safren, Steven A.
ABSTRACT: COVID-19 led to substantial changes in individuals' lives due to preventive measures, including social distancing and "stay at home" orders. One type of social interaction likely impacted is intimacy and sexual relationships. Sexual minority men have long navigated the impact of another pandemic, HIV, on their sexual lives. This study explored the impact of COVID-19 on Latinx sexual minority men's (LSMM) sexual behaviors in South Florida, an HIV and COVID-19 epicenter. A rapid qualitative analysis of semi-structured interviews with LSMM (N = 20) revealed five themes: (1) increased sex with a primary partner, (2) fewer sexual partners, (3) continued pre-COVID-19 sexual activity, often following "quarantine fatigue, " (4) opportunities and challenges related to navigating COVID-19 prevention and sex, and (5) using sexual networking apps in new ways. The findings suggest LSMM's resilience and their ongoing health needs during COVID-19, with implications for interventions to promote LSMM's safe and satisfying sex.